The Influence of Shared Intentions With Others in Physical and Cognitive Tasks That Require Collaborative Solving in Elementary School - Kano, Takahiro; Yokoyama, Keiko; Yamamoto, Yuji (Frontiers in Education, 2022)
Developing the competence to share intentions with others is an important role of elementary schools for the children’s future well-being. We analyzed and clarified the relationship between physical and cognitive tasks that require collaborative solving to cultivate the skill of sharing intentions with others through human movement. As a physical task, we designed a tag game in which two defenders prevented three attackers from passing through to reach the goal line. We focused on the defenders’ movement in the game and analyzed the efficiency of each defender’s movement as an individual behavior and the interpersonal distance between these two defenders as a pair behavior. As a cognitive task, we examined pair activities when understanding concepts in math classes. We observed talking and listening behaviors during the pair activities and analyzed the responsive behavior as an individual behavior, which comprised responsive utterances and active listening from the listener’s gaze direction. Role change during pair activities in math lessons was analyzed as a pair behavior. We then analyzed the relationship between behaviors in both tasks. The hypotheses were as follows: (1) task constraints lead to an interaction between individual and pair behaviors in both tasks and (2) individual and pair behaviors in the two tasks have similar characteristics. The results from both tasks support the first hypothesis that the efficiencies of individual movement and interpersonal distance in the tag game and the frequencies of responsive behavior and role changes in the pair activities in math classes are positively correlated. The results also support the second hypothesis that the individual and pair behaviors in the two tasks are significantly correlated. These results suggest that the competence to share intention with others is fundamental regardless of the task nature: physical or cognitive. The findings suggest that the task constraints of joint action in physical education lead to an understanding of the task goals and to exploring the solution for winning. These experiences might be generalized to all cognitive tasks for cultivating the competence to share intentions with others.